Quelques écueils méthodologiques dans des recherches participatives avec des parents et des professionnels de l’éducation - Dominique Lahanier-Reuter (Recherches en Éducation)
We explore how research focused on the school/parent relationship take families into account. we rely on two ongoing studies, both of which are organized around observations of classes by parents. We thus identify four points which, in our opinion, particularize the place given to families in the research process: the requests of individuals to participate in the research, the designation of the actors, the guarantees provided to maintain these positions, the management of tensions or emotionally strong situations, finally, the positions of the parents during the situations of data collection, interviews, observations, etc.